2006
DOI: 10.1534/genetics.106.061499
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sex and Insulin/Insulin-Like Growth Factor-1 Signaling on Performance in an Associative Learning Paradigm inCaenorhabditis elegans

Abstract: Learning is an adaptive change in behavior in response to environmental stimuli. In mammals, there is a distinct female bias to learn skills that is still unprecedented in other animal taxa. Here we have investigated the biological determinants of performance in an associative learning paradigm in the nematode Caenorhabditis elegans. Using an assay of chemotactic reactions associated with food deprivation, wild-type male worms show inferior learning ability relative to hermaphrodites. Sex-based learning differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 50 publications
2
29
1
Order By: Relevance
“…They proposed that this sex-based learning deficit was the result of reduced insulin/IGF-1 signaling. Consistent with this hypothesis, both Vellai et al (2006) and Tomioka et al (2006) demonstrated a role for insulin-like signaling in the modulation of NaCl preference. NaCl starvation conditioning was defective in worms with mutations in genes encoding homologs of insulin (ins-1), insulin/IGF-I receptor (daf-2), PI 3-kinase (age-1), phosphoinositide-dependent kinase (pdk-1), and Akt/PKB (akt-1).…”
Section: Taste As the Conditioned Stimulussupporting
confidence: 63%
See 1 more Smart Citation
“…They proposed that this sex-based learning deficit was the result of reduced insulin/IGF-1 signaling. Consistent with this hypothesis, both Vellai et al (2006) and Tomioka et al (2006) demonstrated a role for insulin-like signaling in the modulation of NaCl preference. NaCl starvation conditioning was defective in worms with mutations in genes encoding homologs of insulin (ins-1), insulin/IGF-I receptor (daf-2), PI 3-kinase (age-1), phosphoinositide-dependent kinase (pdk-1), and Akt/PKB (akt-1).…”
Section: Taste As the Conditioned Stimulussupporting
confidence: 63%
“…Interestingly, Vellai et al (2006) found that male worms were less proficient at salt starvation learning than hermaphrodites. They proposed that this sex-based learning deficit was the result of reduced insulin/IGF-1 signaling.…”
Section: Taste As the Conditioned Stimulusmentioning
confidence: 99%
“…2 A). The plasticity deficit observed in daf-2(e1370) likely is not attributable to sensory defects, as these mutants have normal benzaldehyde sensation and starvation-induced behaviors (Vellai et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Another series of C. elegans studies suggests that some life-extending treatments improve cognitive function, including performance and memory function, whereas others do not (20,21). In Drosophila, dietary-restricted flies show lifespan extension but no improvement in their cognitive ability (aversion learning test) compared with wild type (22).…”
mentioning
confidence: 99%